Pelatihan Dan Workshop Hijab Lukis Kreatif Dengan Gliter - Chrisdanty, Febry; Wahyulina, Diah (STIE Malangkucecwara, 2025)
PKK or Family Welfare Development, is a movement that focuses on improving the welfare of families and communities in Indonesia. This program accommodates Indonesian women, especially mothers, in terms of empowerment, education, and active participation in community development. One of the main functions of PKK is improving skills and knowledge. In this program, partners are interested in developing the skills of their member mothers, painting on cloth. This program provides solutions in terms of implementing training and also workshops on making painted hijabs with free painting techniques with tools. There are 2 (two) types of activities that will be provided, namely providing training in the form of knowledge about the procedures for making painted hijabs, and workshops on making painted hijabs. This activity is expected to be a means of creativity for partner members. This activity, in addition to being able to provide new business opportunities for partners, can also be a means to reduce stress levels for mothers in carrying out their activities as housewives. The output targets of this activity are first to be a means of proposals for proposers; second to provide solutions to partner problems in terms of facilities and infrastructure for learning painted hijabs; third to improve the knowledge and skills of partner members as a means of empowering women; fourth, the results of the activity will be published in a journal; and the five partners' works will be registered as one of the creations protected by copyright.